Luigi Valadier - González-Palacios, Alvar 1936- (The Frick Collection, 2018)
Of the many artists who flourished in Rome during the eighteenth century, the silversmith Luigi Valadier (1726-1785) was particularly admired by popes, royalty, and aristocrats across Europe. Luigi Valadier: Splendor in Eighteenth-Century Rome, co-curated by Alvar González-Palacios and Xavier F. Salomon, will bring together more than sixty extradordinary works by the renowned silversmith in celebration of his unsurpassed technical expertise and avant-garde aesthetic
Published in conjunction with the exhibition "Luigi Valadier: Splendor in 18th-Century Rome", on view at the Frick Collection, October 30, 2018 - January 20, 2019. - Includes bibliographical references and index
Keywords: Valadier, Luigi -- 1726-1785 -- Exhibitions; Valadier, Luigi -- 1726-1785; Silverwork -- Italy -- Rome -- History -- 18th century -- Exhibitions; Ausstellungskatalog -- Frick Collection -- 30.10.2018-20.01.2019 -- New York, NY